Comparative analysis Delphi research related to Wielkopolska`s innovation - Ragin-Skorecka, Katarzyna; Wyrwicka, Magdalena Krystyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
In article was presented a comparative analysis of the results the Delphi analysis conducted in 2010 and 2014. Problem research was Wielkopolska`s innovation and business networking opportunities, especially in view of 2030. The correspondence analysis and factor analysis was according to the results.